Nanoporous capsules of block co-polymers of [(MeO-PEG-NH)-b-(L-GluA)]-PCL for the controlled release of anticancer drugs for therapeutic applications. (18th February 2016) - Amgoth, Chander; Dharmapuri, Gangappa; Kalle, Arunasree M; Paik, Pradip
Abstract: Herein, new nanoporous capsules of the block co-polymers of MeO-PEG-NH-( L- GluA)10 and polycaprolactone (PCL) have been synthesized through a surfactant-free cost-effective self-assembled soft-templating approach for the controlled release of drugs and for therapeutic applications. The nanoporous polymer capsules are designed to be biocompatible and are capable of encapsulating anticancer drugs (e.g., doxorubicin hydrochloride (DOX) and imatinib mesylate (ITM)) with a high extent (∼279 and ∼480 ng μ g −1, respectively). We have developed a nanoformulation of porous MeO-PEG-NH-( L- GluA)10 -PCL capsules with DOX and ITM. The porous polymer nanoformulations have been programmed in terms of the release of anticancer drugs with a desired dose to treat the leukemia (K562) and human carcinoma cells (HepG2) in vitro and show promising IC50 values with a very high mortality of cancer cells (up to ∼96.6%). Our nanoformulation arrests the cell divisions due to ' cellular scenescence' and kills the cancer cells specifically. The present findings could enrich the effectiveness of idiosyncratic nanoporous polymer capsules for use in various other nanomedicinal and biomedical applications, such as for killing cancer cells, immune therapy, and gene delivery.